The Transmission Mechanisms of Oil Price Fluctuations on Prices - Idriss Iaataren; Ahmed Hefnaoui; Zakaria Ben Darkawi; Mounia Bennani Tannouch (Jurnal Bisnis, Manajemen, dan Ekonomi, 2023)
This paper aims to understand the effects of oil price fluctuations on the real economy and prices, using an ARDL model with quarterly data from 2007 to 2021. The results will help policy makers and economic actors to better understand the transmission mechanisms of oil price fluctuations on the economy and prices, which is important for oil-dependent economies like Morocco. The question is to what extent do oil price fluctuations affect the real economy and price levels in oil import-dependent countries, with a particular focus on the case of Morocco?. The results of the study show that the impact of economic variables on price levels depends on the duration. In the short run, economic growth has a limited inflationary effect, oil price fluctuations have a significant inflationary impact, the nominal exchange rate does not have a significant impact and the openness of the economy does not have a significant impact. In the long run, oil price fluctuations, the real effective exchange rate, and the rate of economic openness have a significant inflationary effect, while economic growth also has an inflationary effect. The competitiveness of the Moroccan economy is important for the stability of price levels in the long run